Variations in maternal vitamin A intake modifies phenotypes in a mouse model of 22q11.2 deletion syndrome. Issue 16 (20th May 2020) - Yitsege, Gelila; Stokes, Bethany A.; Sabatino, Julia A.; Sugrue, Kelsey F.; Banyai, Gabor; Paronett, Elizabeth M.; Karpinski, Beverly A.; Maynard, Thomas M.; LaMantia, Anthony‐S.; Zohn, Irene E.
Abstract: Background: Vitamin A regulates patterning of the pharyngeal arches, cranial nerves, and hindbrain that are essential for feeding and swallowing. In the LgDel mouse model of 22q11.2 deletion syndrome (22q11DS), morphogenesis of multiple structures involved in feeding and swallowing are dysmorphic. We asked whether changes in maternal dietary Vitamin A intake can modify cranial nerve, hindbrain and pharyngeal arch artery development in the embryo as well as lung pathology that can be a sign of aspiration dysphagia in LgDel pups. Methods: Three defined amounts of vitamin A (4, 10, and 16 IU/g) were provided in the maternal diet. Cranial nerve, hindbrain and pharyngeal arch artery development was evaluated in embryos and inflammation in the lungs of pups to determine the impact of altering maternal diet on these phenotypes. Results: Reduced maternal vitamin A intake improved whereas increased intake exacerbated lung inflammation in LgDel pups. These changes were accompanied by increased incidence and/or severity of pharyngeal arch artery and cranial nerve V (CN V) abnormalities in LgDel embryos as well as altered expression of Cyp26b1 in the hindbrain. Conclusions: Our studies demonstrate that variations in maternal vitamin A intake can influence the incidence and severity of phenotypes in a mouse model 22q11.2 deletion syndrome.